Factors affecting compliance rate towards oral nutritional supplements intake among geriatric patients in Hospital Kuala Lumpur - Lo, Adeline Li Ching; Muhammad Rabbani Abdul Malek; Nurshahirah Zulkifli; Siti Nur Fatihah Shaifol Akmar; Chong, Elizabeth Gar Mit; Norzainora Hamsah; Nora Nurlinda Zakaria; Suzana Shahar (Penerbit Universiti Kebangsaan Malaysia, 2019)
Compliance rate towards consumption of oral nutritional supplement (ONS) is low among geriatric patients. Thus, this study aimed to examine factors affecting low compliance of ONS intake among a sample of geriatric patients. A cross-sectional survey was carried out involving 30 geriatric patients being prescribed with ONS during their stay in Hospital Kuala Lumpur. Information on compliance rate and influencing factors were collected through interview and observation. Nutritional status was assessed using anthropometry and Patient Generated Subjective Global Assessment (PG-SGA). 50.0% subjects were underweight and 70.0% and 30.0% were moderate and severely malnourished, respectively. A total of 43.3% were categorised as low, 53.4% medium and 3.3% high compliance towards consumption of ONS. Most of the subjects with low compliance agreed expressed that they need more nursing support (53.8%). Less than half perceived they had been given the needed nursing support (44.4%), and with respect to ONS: knowledgeable (38.5%), timely given (37.5%), understood the importance (35.7%), were able to finish it (35.0%), well-aware of the reasons of prescription (33.3%), satisfied with its taste (33.3%), received suitable volume (33.3%), satisfied with the texture (31.6%), and received suitable frequency (28.6%). In conclusion, approximately 40% of subjects had low compliance towards ONS. Awareness and nursing support were important factors associated with low compliance. There is a need to ensure adequate nursing support and education been given to patients prescribed with ONS in order to increase the compliance rate.